Targeted Therapies for Pediatric AML: Gaps and Perspective - Lonetti, Annalisa; Pession, Andrea; Masetti, Riccardo (Frontiers in Pediatrics, 2019)
Acute Myeloid Leukemia (AML) is a hematopoietic disorder characterized by numerous cytogenetic and molecular aberrations that accounts for approximately 25% of childhood leukemia diagnoses. The outcome of children with AML has increased remarkably over the past 30 years, with current survival rates up to 70%, mainly due to intensification of standard chemotherapy and improvements in risk classification, supportive care, and minimal residual disease monitoring. However, childhood AML prognosis remains unfavorable and relapse rates are still around 30%. Therefore, novel therapeutic approaches are needed to increase the cure rate. In AML, the presence of gene mutations and rearrangements prompted the identification of effective targeted molecular strategies, including kinase inhibitors, cell pathway inhibitors and epigenetic modulators. This review will discuss several new drugs that recently received US Food and Drug Administration approval for AML treatment and promising strategies to treat childhood AML, including FLT3 inhibitors, epigenetic modulators and Hedgehog pathway inhibitors.